Low power SRAM design for 14 nm GAA Si-nanowire technology. Issue 12 (December 2015) - Kaushal, Gaurav; Jeong, H.; Maheshwaram, Satish; Manhas, S.K.; Dasgupta, S.; Jung, S.O.
Abstract: This paper presents a low power and stable 6-T nanowire SRAM cell design by tuning the extension length of the access transistor. Our approach significantly reduces the power dissipation with a low active area and improves the SRAM cell read stability. We utilize device design parameters such as the nanowire diameter, the number of nanowires, and the device extension length to improve the stability of the SRAM cells. We find that the extension length tuning technique exhibits 15% and 60% savings in active area and static power consumption, respectively, in comparison to a conventional multi-nanowire tuning technique. In addition, the proposed technique achieves 6% and 8% improvements in the read and hold noise margins, respectively, with a 6.5% decrease in write noise margin and a 14% increase in the read/write access time. Our results show that the extension length-tuned access transistor is an excellent option for improving the satiability with low power for sub-14-nm technologies.